ESTRUS INDUCTION IN BEETAL GOATS DURING LOW BREEDING SEASON - N. Ahmad; K. Javed; M. Abdullah; A. S. Hashmi and A. Ali (Journal of Animal and Plant Sciences, 2014)
An experiment was conducted during low breeding season on 20 anestrus Beetal goats. These animals were kept at Small Ruminant Training and Research Centre (SRT and RC), University of Veterinary and Animal Sciences, Ravi Campus, Pattoki. The animals were randomly divided in four groups (A, B, C and D) five animals in each group. Group A was considered as negative control by offering only fodder; group B animals were offered fodder and flushing ration (positive control group); group C animals were given fodder along with hormone therapy (0.5ml each of GnRH, PGF2α and GnRH) and goats in group D were fed green fodder, flushing ration (600 gm/animal) and hormone therapy (GnRH, PGF2α and GnRH).This experiment lasted for one month. The reproductive behavior regarding signs of heat, breeding and conception was observed. Blood serum for total protein, albumin, globulin, glucose and urea were analyzed to see the health status of the animals. Data were analyzed by applying ANOVA technique under CRD and differences among treatments were tested by using Duncan’s Multiple Range using SAS 9.1.5. It was observed that estrous induction (60%) was low in group A while conception (80%) and kidding rate (60%) were higher in group B. However, mean birth weight ok kids was higher in group A (3.16±0.76 kg). Twinning percentage was only 20% in A and B groups, whereas, triplet births were also 20% in group D. Mean gestation length was minimum in group B while maximum in group A. The mean values of total protein, globulin and glucose were higher in group A whereas albumin in group C and more urea concentration (36.80±3.23 mg/dL) was observed in animals of group B.
Keywords: Beetal goats; anestrous; reproductive management and serum biochemistry